The Development of an Environment-Based Guided Inquiry Learning Model accompanied by Event Chain to Improve Students' Critical Thinking Skills - Emy Shofiah Setyowati; Sri Yamtinah; Prabang Setyono (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
This study aims to determine the validity, feasibility, and effectiveness of an environment-based guided inquiry learning model accompanied by an Event Chain in improving students' critical thinking skills in Science learning on environmental pollution material. This research is a type of Research and Development that refers to the ADDIE development procedure which encompasses stages including analysis, design, development, implementation, and evaluation. The research subjects were seventh grade students of SMP N 3 Kartasura. This study use instruments in the form of validation sheets, student critical thinking skills tests, and learning modules. Data analysis techniques in the study consisted of validity test, feasibility test, and effectiveness test. The results showed that the learning model developed based on the assessment of seven validators was declared valid and ready to be tested with some improvements in input from the validator. The feasibility test results were feasible with a sig value of 0.00 <0.05, so the developed model had an effect in improving critical thinking skills. The effectiveness test using the N-Gain Score in percent form was 76.33% and it was within the effective category.